PERANCANGAN KONSEP DESAIN KARAKTER PADA PROYEK PEMBELAJARAN CERITA “PETUALANGAN STEVE” - Arfina, Nur Tsamarah; Prasetiya, Happy Yugo (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2023)
Recently, there are still many misconceptions among students in the learning process. Various studies recommend that students can collaborate actively and interactively in a practical approach. PBL (Project-Based Learning) is a project-based learning approach for conducting in-depth investigations of a topic. Each student must produce a product to gain deeper knowledge through active exploration of real-world challenges and problems. This product is related to the Character Design course which requires competence in making character concepts according to stories that have been made before, so as to support student assessment. The entire story concept and character visuals are made suitable for all ages in a light and entertaining way. The purpose of this study is to compile an infographic that contains the character concepts in Petualangan Steve. The research method used is a Design Triangle research method, with a focus on deepening the practice of character concept design which includes verbal information from the story. By designing this character concept, the audience can easily understand the visualization or shape of the character by predicting what the expression, physical form, and other details will look like based on the story concept.